(untitled) (De la Crítica, 2024)
The objective of this research was to generate a theoretical model for the Language, Literature and Latin Education program of the National Experimental University “Francisco de Miranda” (UNEFM). Theoretically supported by the postulates of Descartes (1637/2002), Peirce (1907), Díaz Barriga (1996), and Casarini (2013); among other authors. Oriented under the positivist paradigm, under the Variability of Scientific Research (VIC) system of Padrón (1998); using as a data collection technique a questionnaire survey, applied to twenty-two (22) students and thirty-seven (37) active teachers of said Program; Among the results obtained, the need to update the curricular model around the validity of current social and technological paradigms was reflected. Designing the proposal of a theoretical model for this purpose, representing an innovative alternative for the strengthening of this UNEFM academic program.